The Effect of Multichannel and Channel-Free Hearing Aids on Spectral-Temporal Resolution and Speech Understanding in Noise - Kılıç, Mert; Kara, Eyyup (Journal of the American Academy of Audiology, 2022)
Background Identifying and understanding speech is difficult for individuals with sensorineural hearing loss, especially in noisy environments. Possible causes include less audibility of the signal, impaired temporal resolution, and low selectivity of frequency. The hearing aid is the most common option used to minimize the problems faced by individuals with sensorineural hearing loss.Purpose This article investigates the effects of multichannel and channel-free hearing aid signal processing techniques on spectral-temporal resolution and speech understanding in noise.Research Design An experimental study was used in which the determined tests were applied to the participants.Study Sample Thirty-four individuals with bilateral symmetrical sensorineural hearing loss between the ages of 18 and 70 were included in our study.Data Collection and Analysis Spectral-temporally modulated ripple test, random gap detection test (RGDT), and Turkish matrix test were applied to the participants using multichannel and channel-free hearing aids. All the data obtained were compared statistically in terms of the performances of the hearing aids.Results There was no significant difference between multichannel and channel-free hearing aids for spectral resolution and speech understanding in noise tests (p > 0.05). While there was no significant difference between the two hearing aids for 500 and 4,000 Hz RGDT in temporal resolution measurement (p > 0.05), for 1,000 Hz (p = 0.045), 2,000 Hz (p = 0.046), and composite RGDT (p = 0.001), statistically significant better performances were obtained with the channel-free hearing aids.Conclusion It is thought that faster processing of the incoming signal in the channel-free hearing aids improves the temporal resolution performance. It is predicted that our study findings might help to determine the signal processing technique that will maximize the communication skills of the patients in various conditions.
Keywords: multichannel hearing aid; channel-free hearing aid; speech in noise; spectral resolution; temporal resolution